KENDALA DAN MASALAH DALAM PROSES PEMBELAJARAN MATEMATIKA KELAS 5 DI UPT SDN 009 BANGKINANG - Rizki Ananda; Putri Suzila Aini; Nadia Salsabilla; Putri Yani; Marvini Al-Fikamza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to identify the obstacles and problems faced by teachers in the process of learning mathematics for grade 5 at UPT SDN 009 Bangkinang. The method used in this study was the interview method. The results of this study indicate that many grade 5 children are less active and do not have the enthusiasm to learn mathematics and there are constraints of insufficient time for teachers to teach mathematics. Teachers must have their own way to make children enthusiastic and how to adjust the material to limited lesson hours.